Effect of Employee Demographic Characteristics and Family/Work Conflict on Organizational Commitment Among the Police Officers in Nakuru County, Kenya. - Lekaram, Esther; Kipkebut, Dr. Dinah J. (International Journal of Scientific Research and Management (IJSRM), 2019)
This paper examines the demographic characteristics and related variables on family/work conflict among the Police Officers in Nakuru County, Kenya.  The participants were from eight (8) Police Division and a simple random sample of 170 was derived from a total number of 278 Officers.  The level of conflict that employees perceive between their working and personal lives on organizational commitment was based on their personal characteristics which included: gender, marital status, age, level of education, tenure and number of hours worked among the police officers. The report suggested that the biographical personal characteristics suggested that those who participated there were more male officers compared to the female gender. The results showed that more female police officers experienced more stress than men which spill into their work due to the multiple roles they play as wives, mothers, care givers, family career as well as employees.  The results are discussed in terms of marital status, level of education, tenure of service and numbers of hours worked per day on how they influence organizational commitment among the police officers in Nakuru County, Kenya